Research on children abuse in Lithuania and its importance for prevention of juvenile crime - Rokas Uscila (Temida)
The main goal of this paper is to present an overview of children victims’ situation in Lithuania and to reveal possible forms and effects of inversion of victim - child and offender. The article presents an analysis of official statistic of 2004 on children victimization in Lithuania and invokes data of several selective researches in the area. It defines the conception of inversion of victim and offender, presents certain kinds, types and classifications of inversion. An analysis of accumulative and cyclical inversion of victim - child and offender from the perspective of victimology is introduced. The author presents the inversion of victim - child and offender as a dynamic phenomenon, as a result of interaction between the processes of criminalization and victimization. Victimology, having a unique target of research, analyses the phenomenon of the inversion of participants or participant of victimic event, which has not been given adequate focus in law or other social sciences, although it is very important in organizing educational process.